Individual and Social Risk during Transportation of Dangerous Substances - Zdenek Dvorak; Pavel Fuchs; Jan Novak; Radovan Sousek (Communications - Scientific letters of the University of Zilina, 2011)
This article aims to present new views on risk assessment, primarily individual and social risks during transportation of dangerous substance. Included are modelling procedures and methods applied to calculate dangerous substance exposure to the biodiversity of the environment, solved in project BIOTRA. New procedures and methods applied for calculation of environmental exposure by dangerous substance outflows in road transport are also presented.